Determination of Photoneutron Production from Different Targets Irradiated by Electron Beam - Melyan, E.; Katovský, K.; Mukherjee, S.
In the present work, a study has been conducted to estimate the production of photoneutrons from different targets irradiated by a 70 MeV electron beam. The linear electron accelerator at the Yerevan Physics Institute in Armenia was used for the purpose. The reaction rates were determined through detailed off-line analysis of experimental data and subsequently compared to theoretical predictions by using the MCNP (Monte Carlo N-Particle Transport) and Cascade Exciton Physics Model (CEM03.03) codes.
Keywords: Physics